Silicon-carbon negative electrode material and preparation method, application, negative electrode sheet, lithium-ion battery

By building a compatible connection layer and an ion conductor layer on the surface of the silicon carbon material matrix, the problems of uneven coating and large lithium ion transmission barrier of silicon carbon material in sulfide all-solid state batteries are solved, and the high cycle stability and rate performance of the battery are achieved.

CN119764386APending Publication Date: 2025-04-04BEIJING WELION NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411936099.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing silicon carbon materials have problems such as uneven coating, affecting performance of silicon grain growth, and large lithium ion transmission barriers in sulfide all-solid state batteries, resulting in limited performance performance.

Method used

By constructing a compatible connection layer and an ionic conductor layer on the surface of the silicon-carbon material matrix, the Li+ transmission barrier at the material interface is reduced, and side reactions such as electrolyte decomposition are reduced, thereby improving the cycle stability and rate performance of the battery.

Benefits of technology

The stable core-shell structure of silicon carbon anode material is realized, forming a uniform double cladding layer, which significantly improves the cycle stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764386A_ABST
    Figure CN119764386A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-carbon negative electrode material, a preparation method and application thereof, a negative electrode plate, and a lithium ion battery. The silicon-carbon negative electrode material comprises a silicon-carbon material matrix, and a compatible connecting layer and an ion conductor layer sequentially coated on the surface of the matrix; the compatible connecting layer is a partially carbonized conductive polymer and a remaining conductive polymer, and the ion conductor layer is a conductive polymer containing LiF and Li α M β O γ A composite, wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time; the silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.3-2.2. The silicon-carbon negative electrode material improves Li under the premise of ensuring its intrinsic performance. + Transfer dynamics, greatly improving the battery's cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a silicon-carbon negative electrode material, a method for preparing the silicon-carbon negative electrode material, an application of the silicon-carbon negative electrode material, a negative electrode sheet containing the silicon-carbon negative electrode material, and a lithium-ion battery containing the silicon-carbon negative electrode material. Background Art

[0002] In recent years, the new energy vehicle industry has developed rapidly, and its core lies in the continuous iteration and upgrading of key component technologies with power batteries as the core. The current power battery industry dominated by lithium-ion batteries still has problems such as low energy density and poor safety, which has become a huge obstacle to the development of new energy vehicles. The development of all-solid-state lithium-ion batteries with high energy density and high safety performance is on the agenda, and sulfide all-solid-state batteries are considered one of the best routes due to their high ionic conductivity and easy processing characteristics. However, traditional graphite negative electrode materials cannot meet the needs of high-energy-density sulfide all-solid-state batteries due to their low mass-to-capacity ratio (372mAh / g), and higher-capacity negative electrode materials are urgently needed.

[0003] Vapor-deposited silicon-carbon materials stand out among many negative electrode materials because of their extremely high mass specific capacity (>2000mAh / g), low expansion, and stable structure, and are expected to become the core negative electrode material for high-energy-density sulfide all-solid-state batteries. However, the new vapor-deposited silicon-carbon materials have a high carbon content and low carbon crystallinity, and face the following problems in sulfide all-solid-state battery applications: First, the exposure of low-crystalline carbon easily catalyzes the decomposition of sulfide solid electrolytes and accelerates the growth of SEI; second, the lithium ion transmission barrier between the silicon-carbon material and the sulfide electrolyte interface is large, thereby increasing the internal polarization of the battery. The existence of the above problems seriously restricts the performance of silicon-carbon materials in sulfide all-solid-state batteries.

[0004] In the prior art, for the application of silicon-carbon negative electrode material system in solid-state batteries, most of the above-mentioned problems are alleviated by surface modification strategies. For example, CN118016985A adds silicon-carbon powder to a solid electrolyte suspension, heats and stirs it to a dry powder, and uses laser sintering to obtain a porous silicon-carbon material coated with a solid electrolyte layer to limit the expansion of silicon, improve electrical conductivity and high-density lithium storage capacity. At the same time, the solid electrolyte after laser sintering is coated on the porous silicon-carbon surface to improve ion conduction, effectively promote the formation of a stable SEI film in the negative electrode, and improve the battery cycle performance. However, the introduction of the solid electrolyte suspension makes it difficult to form a complete and uniform coating layer on the silicon-carbon surface, and the coating effect is not good; secondly, the ultra-high instantaneous heat release of the laser sintering treatment method will also cause the internal amorphous silicon particles to further crystallize and grow, seriously affecting its cycle performance.

[0005] CN118039910A uses organic aluminum salt and organic base to deposit porous aluminum oxide on the surface of silicon-carbon precursor material through chemical precipitation and high-temperature sintering and carbonization treatment, and then uses lithium sheet pre-lithium reaction to form lithium aluminate, and finally realizes lithium aluminate coating of silicon-carbon precursor material, aiming to improve rate performance and first efficiency. Among them, the lithium aluminate coating layer is a porous structure and needs to be sintered at high temperature. There are still problems such as uneven surface coating layer and growth of core silicon grains leading to poor performance. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of uneven coating / single coating / poor compatibility of existing silicon-carbon materials, silicon grain growth affecting the intrinsic performance of silicon-carbon materials, and the interface side reaction easily generated when silicon-carbon materials contact electrolytes, and to provide a silicon-carbon negative electrode material, a method for preparing a silicon-carbon negative electrode material, an application of a silicon-carbon negative electrode material, a negative electrode sheet, and a lithium-ion battery. The silicon-carbon negative electrode material, while ensuring its intrinsic performance, can reduce the interface Li + Transmission barrier, improving Li + Transfer kinetics, reduce the occurrence of side reactions such as electrolyte decomposition, and thus greatly improve the cycle stability and rate performance of the battery.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a silicon-carbon negative electrode material, which comprises a silicon-carbon material matrix, and a compatible connecting layer and an ion conductor layer sequentially coated on the surface of the matrix; the compatible connecting layer is a partially carbonized conductive polymer and the remaining conductive polymer, and the ion conductor layer is a conductive polymer containing LiF and Li α M β O γ A complex of, wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time;

[0008] The silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.3-2.2, and I(D) and I(G) respectively represent the silicon-carbon negative electrode material in the Raman spectrum, corresponding to 1330-1370cm -1 and 1560-1610cm -1 The intensity of characteristic peak D and characteristic peak G in the wavenumber range.

[0009] In the present invention, unless otherwise specified, the silicon-carbon negative electrode material has a core-shell structure, that is, the silicon-carbon material matrix is ​​used as the core, the compatible connecting layer is used as the inner shell, and the ion conductor layer is used as the outer shell.

[0010] In the present invention, unless otherwise specified, the partially carbonized conductive polymer refers to a conductive polymer partially carbonized product that mainly exists in the form of elemental carbon.

[0011] In the present invention, unless otherwise specified, the intensity of characteristic peak D and characteristic peak G refers to the peak height.

[0012] The silicon-carbon negative electrode material provided by the present invention has a Raman spectrum of 1330-1370cm -1 The characteristic peak D in the wavenumber range is mainly attributed to carbon D, indicating the carbon atom lattice defect, and its intensity is proportional to the degree of disorder of the carbon material; 1560-1610cm -1 The characteristic peak G in the wavenumber range is mainly attributed to carbon G, indicating the degree of graphitization of carbon materials.

[0013] In the present invention, unless otherwise specified, in the silicon-carbon negative electrode material, I(D) / I(G) represents the degree of carbonization of the conductive polymer in the compatible connecting layer, that is, part of it is carbonized and the remaining part still exists in the form of a conductive polymer. At the same time, as the ratio of I(D) / I(G) decreases, the electronic conductivity of the silicon-carbon negative electrode material increases.

[0014] In the present invention, electrical conductivity refers to ionic conductivity and electronic conductivity.

[0015] The inventors of the present invention have found that: a compatible connecting layer and an ion conductor layer are sequentially coated on the surface of a silicon-carbon material substrate, and the interfacial side reactions are reduced by isolating the silicon-carbon material substrate from direct contact with the electrolyte, especially the sulfide electrolyte, thereby avoiding the loss of capacity and first effect; specifically, the introduction of the ion conductor layer reduces the lithium ion transmission energy barrier, improves the lithium ion transmission dynamics, and thus improves the battery rate performance; the introduction of the compatible connecting layer causes the product of partial carbonization of the conductive polymer to exist mainly in the form of elemental carbon, which helps to improve the electronic conductivity of the material, thereby improving the battery rate performance, and the remaining part exists in the form of a polymer, one end of which can cross-link with the surface of the silicon-carbon material substrate to form a chemical bond, and the other end is interlocked with the ion conductor layer, thereby constructing a bridge and bond between the surface of the silicon-carbon material substrate and the ion conductor layer, which helps to enhance the interfacial bonding force between the two, enhances the contact tightness of the solid-solid interface, and also realizes the slow release of stress from the inside to the outside.

[0016] Therefore, by giving full play to the synergistic effect between the compatible connecting layer and the ion conductor layer, the silicon-carbon negative electrode material has a stable core-shell structure, forming a stable and uniform double coating layer (that is, the inner coating layer is the compatible connecting layer, and the outer coating layer is the ion conductor layer), thereby achieving a significant improvement in the battery's cycle stability and rate performance.

[0017] A second aspect of the present invention provides a method for preparing a silicon-carbon negative electrode material, the preparation method comprising:

[0018] (1) mixing a dispersion containing a conductive polymer with a silicon-carbon material matrix and performing a first drying to load the conductive polymer on the surface of the silicon-carbon material matrix to obtain a first intermediate;

[0019] (2) mixing the dispersion containing the metal salt mixture with the first intermediate and performing a second drying to load the metal salt mixture on the surface of the first intermediate to obtain a second intermediate;

[0020] (3) sintering the second intermediate in an inert atmosphere so that the conductive polymer is partially carbonized and the metal salt mixture is in situ converted into a catalyst containing LiF and Li α M β O γ A composite of a silicon-carbon anode material and a compatible connecting layer and an ion conductor layer are formed; wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time;

[0021] Wherein, the sintering temperature T> the melting point T of the metal salt mixture m , and the initial decomposition temperature of the conductive polymer is T d1 <the sintering temperature T<the complete decomposition temperature T of the conductive polymer d2 .

[0022] The third aspect of the present invention provides an application of the silicon-carbon negative electrode material provided in the first aspect, or the silicon-carbon negative electrode material prepared by the preparation method provided in the second aspect in a lithium ion battery.

[0023] A fourth aspect of the present invention provides a negative electrode plate, which contains the silicon-carbon negative electrode material provided by the first aspect, or the silicon-carbon negative electrode material prepared by the preparation method provided by the second aspect.

[0024] A fifth aspect of the present invention provides a lithium-ion battery, comprising: a positive electrode plate, an electrolyte, and the negative electrode plate provided by the fourth aspect.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The silicon-carbon negative electrode material provided by the present invention comprises a compatible connecting layer and an ion conductor layer sequentially coated on the surface of the substrate. On the one hand, the direct contact between the silicon-carbon material substrate and the electrolyte interface can be isolated, which significantly reduces the interface side reaction, thereby improving the reversible capacity and the first coulombic efficiency of the material; on the other hand, the compatible connecting layer and the ion conductor layer also have a certain mechanical strength, which is conducive to alleviating the volume expansion of the silicon-carbon material, thereby ensuring the integrity of the silicon-carbon material structure and improving the cycle performance;

[0027] At the same time, the silicon-carbon negative electrode material provided by the present invention, by limiting the I(D) / I(G) ratio and regulating the degree of carbonization in the compatible connecting layer, not only increases the bonding force at the interface between the ion conductor layer and the silicon-carbon material matrix, increases the contact tightness of the solid-solid interface, but also realizes the slow release of stress from the inside to the outside; it also improves the conductivity of the material, thereby improving the rate performance of the battery.

[0028] (2) The preparation method provided by the present invention first loads a conductive polymer and a metal salt mixture on the surface of a silicon-carbon material substrate in sequence, and then uses a specific temperature sintering to partially carbonize the conductive polymer to construct a compatible connecting layer as an inner coating layer, and at the same time, the metal salt mixture is in situ converted into a LiF and Li α M β O γ The composite is used to construct an ion conductor layer as an outer coating layer; in particular, by adjusting the sintering temperature range, the carbonization degree of the compatible connecting layer, that is, the characteristic peak I(D) / I(G) ratio of the silicon-carbon negative electrode material, is adjusted;

[0029] At the same time, the present invention adopts a low-temperature sintering process. During the sintering process, the amorphous silicon particles inside the silicon-carbon material matrix will not further crystallize and grow, and the intrinsic properties of the silicon-carbon material matrix can be retained.

[0030] (3) Compared with the existing single coating layer with poor interface compatibility with the substrate, which makes it difficult to achieve uniform and effective coating, the present invention introduces two different functional coating layers, namely, a compatible connecting layer with a bridging effect and an ion conductor layer with a function of reducing the lithium ion transmission barrier, to give full play to the synergistic effect between the two and effectively improve the electrochemical performance of the battery, especially the first efficiency, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the cross-sectional structure of the silicon-carbon negative electrode material provided by the present invention;

[0032] Figure 2 XRD pattern of the silicon-carbon material substrate P1 provided in Example 1;

[0033] Figure 3 The DSC graph of the metal salt mixture and the conductive polymer provided in Example 1;

[0034] Figure 4 This is a SEM image of the silicon-carbon negative electrode material S1 prepared in Example 1;

[0035] Figure 5 This is the EDS distribution image of the silicon-carbon negative electrode material S1 prepared in Example 1;

[0036] Figure 6 The Raman spectrum of the silicon-carbon negative electrode material S1 prepared in Example 1;

[0037] Figure 7 This is a rate-cycle performance diagram of a sulfide solid-state half-cell assembled from the silicon-carbon negative electrode material S1 prepared in Example 1. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] In the present invention, unless otherwise specified, "first" and "second" do not indicate a sequence or limit the materials or steps, but are only used to distinguish or indicate that they are not the same material or step. For example, "first" and "second" in "first intermediate" and "second intermediate" are only used to indicate that they are not the same intermediate.

[0040] The first aspect of the present invention provides a silicon-carbon negative electrode material, which comprises a silicon-carbon material substrate, and a compatible connecting layer and an ion conductor layer sequentially coated on the surface of the substrate; the compatible connecting layer is a partially carbonized conductive polymer and a remaining conductive polymer, and the ion conductor layer is a conductive polymer containing LiF and Li α M β O γ A complex of, wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time;

[0041] The silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.3-2.2, and I(D) and I(G) respectively represent the silicon-carbon negative electrode material in the Raman spectrum, corresponding to 1330-1370cm -1 and 1560-1610cm -1 The intensity of characteristic peak D and characteristic peak G in the wavenumber range.

[0042] In the present invention, unless otherwise specified, in the Raman spectrum, the silicon-carbon negative electrode material has a wavelength of 1330-1370 cm -1 and 1560-1610cm -1 There is a Raman response within the wavenumber range, corresponding to characteristic peak D and characteristic peak G respectively; I(D) / I(G) represents the intensity ratio of characteristic peak D and characteristic peak G in the Raman spectrum of the silicon-carbon negative electrode material, that is, the peak height ratio of characteristic peak D and characteristic peak G.

[0043] In some embodiments of the present invention, preferably, based on the total weight of the silicon-carbon material matrix, the silicon content is 45-65wt%, for example, 45wt%, 50wt%, 55wt%, 58wt%, 60wt%, 62wt%, 65wt%, and any value in the range consisting of any two numerical values, preferably 50-60wt%; the carbon content is 35-55wt%, for example, 35wt%, 38wt%, 40wt%, 42wt%, 45wt%, 50wt%, 55wt%, and any value in the range consisting of any two numerical values, preferably 40-50wt%.

[0044] In the present invention, unless otherwise specified, the sum of the silicon content and the carbon content in the silicon-carbon material matrix is ​​100 wt %.

[0045] In some embodiments of the present invention, preferably, the D of the silicon-carbon material matrix 50 It is 1-15 μm, for example, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, and any value in a range consisting of any two values, and is preferably 3-8 μm.

[0046] In the present invention, D 50 The parameters were measured using a Malvern 3000 laser particle size analyzer.

[0047] In some embodiments of the present invention, preferably, the tap density of the silicon-carbon material matrix is ​​0.5-2 g / cm 3 , for example, 0.5 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 2g / cm 3 , and any value in the range of any two values, preferably 0.81.2g / cm 3 .

[0048] In the present invention, the tap density parameter is measured using a tap density meter.

[0049] In some embodiments of the present invention, preferably, the specific surface area of ​​the silicon-carbon material matrix is ​​0.55 m 2 / g, for example, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, and any value in the range of any two values, preferably 0.5-3m 2 / g.

[0050] In the present invention, the specific surface area parameter is measured using the nitrogen isothermal adsorption-desorption curve using the BJH equation.

[0051] In the present invention, the type of the silicon-carbon material matrix has a wide range of choices, as long as it meets the above definition. Preferably, the silicon-carbon material matrix includes porous carbon and amorphous silicon located inside the porous carbon. In the present invention, the grain size of the amorphous silicon is less than 2nm.

[0052] In some embodiments of the present invention, preferably, the specific surface area of ​​the porous carbon is ≥1500m 2 / g, for example, 1500m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, 2100m 2 / g, 2200m 2 / g, and any value in the range of any two values, preferably 1700-2200m 2 In the present invention, the porous carbon meeting the above specific surface area range has a rich pore structure on the one hand, and reserves sufficient space for the deposition of amorphous silicon on the other hand.

[0053] In some embodiments of the present invention, preferably, the pore volume of the porous carbon is 0.75-1.05cc / g, for example, 0.75cc / g, 0.8cc / g, 0.82cc / g, 0.85cc / g, 0.88cc / g, 0.9cc / g, 0.92cc / g, 0.95cc / g, 1.00cc / g, 1.05cc / g, and any value in the range composed of any two values, preferably 0.8-0.95cc / g.

[0054] In the present invention, porous carbon, as a carrier of amorphous silicon, mainly plays an important role in accommodating amorphous silicon. The pore volume represents the volume of the pores in the porous carbon. The larger the volume, the more deposition sites of amorphous silicon. Under the condition of the same silicon deposition amount, within the above-mentioned limited range, the larger the pore volume, the more space can be reserved for the expansion of amorphous silicon, which is conducive to reducing the expansion of the material. However, when the pore volume is too large, the strength of the matrix will be affected, that is, the insufficient strength of the matrix particles is easy to break during rolling, affecting the structural integrity.

[0055] In the present invention, the pore volume parameter is calculated using the BET method, that is, nitrogen or argon is adsorbed on the sample at low temperature and the adsorption isotherm data are used.

[0056] In some embodiments of the present invention, preferably, the microporosity / mesoporosity of the porous carbon is ≥4, for example, 4, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, preferably 5-7; wherein, microporosity refers to the volume ratio of micropores with a pore size of <2nm to the total pore volume, that is, the ratio of the volume of micropores with a pore size of <2nm to the total pore volume, and mesoporosity refers to the volume ratio of mesopores with a pore size of 2-50nm to the total pore volume, that is, the ratio of the volume of mesopores with a pore size of 2-50nm to the total pore volume. In the present invention, porous carbon is used as a carrier of amorphous silicon, and its pore structure is the deposition site of amorphous silicon.

[0057] In the present invention, the above-mentioned silicon-carbon material matrix is ​​prepared by vapor deposition. The preparation process can be simply understood as introducing silicon source gas into porous carbon, and the silicon source gas is adsorbed by the micropores in the porous carbon, and then gradually decomposes to form amorphous silicon. The whole process follows the mechanism that the silicon source gas is first adsorbed by the micropores, and then decomposed into amorphous silicon deposited in the pores (adsorption-decomposition). Therefore, the present invention limits the ratio of micropores / mesopores of porous carbon. If this ratio is too small, it means that the micropores in the porous carbon are too small, and it is difficult to achieve effective adsorption of silicon source gas, resulting in problems such as low utilization of silicon source gas, and too many mesopores may cause problems such as decreased particle strength.

[0058] In the present invention, the porous carbon is selected from raw materials for producing activated carbon, including but not limited to resin-based porous carbon, biomass-based porous carbon, petroleum coke-based porous carbon and derivatives thereof.

[0059] In some embodiments of the present invention, preferably, the silicon-carbon material matrix further includes a carbon layer located on the surface of the porous carbon.

[0060] In some embodiments of the present invention, preferably, the thickness of the carbon layer is 2-10 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, and any value in the range consisting of any two values, preferably 3-8 nm.

[0061] In the present invention, the thickness parameter is measured by TEM.

[0062] In a specific embodiment of the present invention, the silicon-carbon material matrix includes porous carbon, amorphous silicon located inside the porous carbon, and a carbon layer located on the surface of the porous carbon.

[0063] In some embodiments of the present invention, preferably, the cross-sectional schematic diagram of the silicon-carbon negative electrode material is as follows Figure 1 As shown, it includes a silicon-carbon material matrix as a core, a compatibility connecting layer as an inner cladding layer, and an ion conductor layer as an outer cladding layer; wherein the silicon-carbon material matrix includes a silicon-carbon matrix and an optional carbon layer, and the silicon-carbon matrix is ​​composed of porous carbon and amorphous silicon located inside the porous carbon.

[0064] In some embodiments of the present invention, the silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.3-2.2, for example, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.8, 2, 2.2, and any value in the range of any two values, preferably 0.4-1.5, more preferably 0.5-1.2.

[0065] In the present invention, I(D) / I(G) represents the carbonization degree of the conductive polymer. When the above range is met, on the one hand, the interfacial bonding force between the silicon-carbon material matrix and the ion conductor layer is enhanced, the contact tightness of the solid-solid interface is enhanced, and the stress is slowly released from the inside to the outside. On the other hand, it is beneficial to improve the conductivity of the silicon-carbon material matrix, thereby improving the rate performance of the battery.

[0066] In the present invention, when I(D) / I(G)>2.2, the carbonization degree of the conductive polymer is too low or not carbonized, thereby reducing the conductivity of the silicon-carbon negative electrode material and the rate performance of the battery; when I(D) / I(G)<0.3, the carbonization degree of the conductive polymer is too high, reducing the interfacial bonding force between the matrix and the ion conductor layer, affecting the structural stability of the silicon-carbon negative electrode material, and thereby reducing the cycle performance of the battery.

[0067] In the present invention, unless otherwise specified, the characteristic peak curves of I(D) and I(G) are measured by a Raman spectrometer, which is mainly used to characterize the structural properties of carbon materials on the surface of materials in the study of lithium battery materials.

[0068] In some embodiments of the present invention, preferably, in the compatible connecting layer, one end of the remaining conductive polymer forms a chemical bond with the silicon-carbon material matrix through cross-linking, including but not limited to -OH, Si-OH, Si-NH2, -CO, C=O, -CF3, -CN, etc., and the other end can be interlocked with the ion conductor layer, acting as a bridge and link between the silicon-carbon material matrix and the ion conductor layer, which helps to enhance the bonding force between the two.

[0069] In some embodiments of the present invention, preferably, the conductivity of the conductive polymer is 0.01-120 S / cm, for example, 0.01 S / cm, 0.05 S / cm, 0.1 S / cm, 1 S / cm, 2 S / cm, 5 S / cm, 10 S / cm, 15 S / cm, 20 S / cm, 30 S / cm, 50 S / cm, 60 S / cm, 80 S / cm, 90 S / cm, 100 S / cm, 120 S / cm, and any value in the range consisting of any two values, preferably 0.1-100 S / cm.

[0070] In the present invention, the conductivity parameters are measured using a powder resistivity meter; meanwhile, the conductivity parameters are measured at room temperature, which is 25±2°C.

[0071] In some embodiments of the present invention, preferably, the weight average molecular weight of the conductive polymer is 10 2 -10 6 g / mol, for example, 10 2 g / mol, 10 3 g / mol, 2×10 3 g / mol, 5×10 3 g / mol, 1×10 4 g / mol, 2×10 4 g / mol, 5×10 4 g / mol, 8×10 4 g / mol, 1×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 1×10 6 g / mol, and any value in the range of any two values, preferably 10 3 -10 5 g / mol.

[0072] In the present invention, "weight average molecular weight (Mw)" refers to a conversion value relative to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value obtained by converting a value measured using GPC under the following conditions, and a calibration curve is prepared using standard polystyrene of an Agilent system.

[0073] In some embodiments of the present invention, preferably, the conductive polymer is selected from at least one of polypyrrole (PPy), polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT), polypyridine, polyacetylene, polyparaphenylene vinylene, modified polyacrylic acid, polythiophene, polyfuran, polycarbazole, polyphenylene sulfide and cross-linked polymers thereof.

[0074] In the present invention, polyaniline is not particularly limited, and polyaniline that is doped and modified according to a known method in the art or unmodified can be used in the present invention. The polyaniline doping and modification methods include chemical doping and mechanical modification.

[0075] In the present invention, modified polyacrylic acid includes but is not limited to doped polyacrylic acid, chemically modified polyacrylic acid, oxidized polyacrylic acid, composite materials containing polyacrylic acid, and the like.

[0076] In the present invention, doping polyacrylic acid refers to mixing polyacrylic acid with a conductive polymer material / conductive filler to form a conductive network; for example, polystyrene sulfonate (PSS) or polythiophene can make polyacrylic acid have conductive properties.

[0077] In the present invention, chemically modifying polyacrylic acid refers to introducing a functional group having a conductive property, such as a conductive π-conjugated structure, and connecting it to the polyacrylic acid molecule by a chemical modification method, thereby making it have a conductive property.

[0078] In the present invention, oxidized polyacrylic acid refers to oxidized polyacrylic acid that can introduce oxygen-containing functional groups to increase the possibility of intramolecular or intermolecular electron transfer, thereby improving conductivity.

[0079] In the present invention, the composite material containing polyacrylic acid refers to a composite material having conductivity formed by compounding polyacrylic acid with conductive nanomaterials (such as carbon nanotubes, conductive polymers, metal nanoparticles, etc.).

[0080] In the present invention, the cross-linked polymer refers to a cross-linked polymer of a conductive polymer and a non-conductive polymer / compound, including but not limited to TPA-PEDOT, PEDOT-PSS, etc. In the present invention, TPA refers to 4-amino-p-terphenyl; PSS refers to polystyrene sulfonate.

[0081] In the present invention, the ion conductor layer contains LiF and Li α Mβ O γ A complex of , wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time.

[0082] In the present invention, β and γ are not 0 at the same time, which means β=0 and γ≠0; or β≠0 and γ=0; or β≠0 and γ≠0.

[0083] In some embodiments of the present invention, preferably, in the composite, Li α M β O γ Selected from Li2O, Li3P, Li3PO4, L2S, Li2SO4 and Li x B y O z At least one of, wherein 1≤x≤3, 1≤y≤4, 2≤z≤7. In the present invention, Li x B y O z Including but not limited to lithium borate (Li3BO3), lithium metaborate (LiBO2), lithium pyroborate (Li2B4O7), etc.

[0084] In some embodiments of the present invention, it is further preferred that in the composite, LiF and Li α M β O γ The molar ratio is 1:(0.05-1), for example, 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.12, 1:0.15, 1:0.18, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.8, 1:1, and any value in the range consisting of any two values, preferably 1:(0.06-0.6).

[0085] In some embodiments of the present invention, preferably, the composite is prepared by sintering a metal salt mixture containing at least Li, F, M, and O in an inert atmosphere.

[0086] In the present invention, the inert atmosphere includes but is not limited to nitrogen atmosphere, helium atmosphere, argon atmosphere, neon atmosphere, etc., preferably nitrogen atmosphere.

[0087] In the present invention, the type of the metal salt mixture has a wide range of choices, as long as it is converted into a mixture containing LiF and Li α M β O γPreferably, the metal salt mixture is selected from at least two of LiOH, LiNO3, Li2CO3, LiBF4, LiPF6, Li2C2O4, LiBOB, LiODFB, LiDFP, LiTFSI, Ca(TFSI)2 and Mg(TFSI)2.

[0088] In the present invention, LiBOB is lithium bis(trifluoromethanesulfonyl)imide; LiODFB is lithium difluoroborate; LiDFP is lithium difluorophosphate; LiTFSI is lithium bis(trifluoromethanesulfonyl)imide; Ca(TFSI)2 is calcium bis(trifluoromethanesulfonyl)imide; and Mg(TFSI)2 is magnesium bis(trifluoromethanesulfonyl)imide.

[0089] In the present invention, the composite is prepared by sintering a metal salt mixture, and the melting point of the composite is higher than the melting point of the metal salt mixture and the sintering temperature. Preferably, the melting point T' of the composite is m > the sintering temperature T > the melting point T of the metal salt mixture m .

[0090] In some embodiments of the present invention, preferably, the sintering temperature T> the melting point T of the metal salt mixture m , and the initial decomposition temperature of the conductive polymer is T d1 <the sintering temperature T<the complete decomposition temperature T of the conductive polymer d2 This arrangement ensures that both LiF and Li α M β O γ The composite is formed and the conductive polymer is partially carbonized.

[0091] In some embodiments of the present invention, further preferably, the melting point T m ≤400°C, for example, 400°C, 380°C, 350°C, 300°C, 280°C, 250°C, 220°C, 200°C, 180°C, 150°C, and any value in the range consisting of any two values, preferably 180-380°C.

[0092] In some embodiments of the present invention, preferably, the thickness of the compatible connecting layer is 1-10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, and any value in the range consisting of any two values, preferably 2-5 nm.

[0093] In some embodiments of the present invention, preferably, the thickness of the ion conductor layer is 1-10 nm, for example, 1 nm, 2 nm, 2.2 nm, 2.5 nm, 2.8 nm, 3 nm, 3.2 nm, 3.5 nm, 3.8 nm, 4 nm, 5 nm, 8 nm, 10 nm, and any value in a range consisting of any two values, preferably 2-4 nm.

[0094] In some embodiments of the present invention, preferably, the ionic conductivity of the silicon-carbon negative electrode material is ≥10 -8 S / cm, preferably 10 -8 -10 -7 S / cm, for example, 10 -8 S / cm, 1×10 -8 S / cm, 2×10 -8 S / cm, 3×10 -8 S / cm, 4×10 -8 S / cm, 5×10 -8 S / cm, 8×10 -8 S / cm, 1×10 -7 S / cm, and any value in the range consisting of any two values.

[0095] In the present invention, the ionic conductivity parameter is measured by an AC impedance method, including: sandwiching the sample to be tested between two stainless steel disk electrodes (SS), measuring the ionic conductivity (σ) by electrochemical impedance spectroscopy (EIS), and calculating according to formula (1): Among them, R b is the volume resistance of the sample to be tested (R b Determined by impedance spectrum), L and S are the thickness and area of ​​the sample to be tested.

[0096] In some embodiments of the present invention, preferably, the electronic conductivity of the silicon-carbon negative electrode material is ≥0.01S / cm, for example, 0.01S / cm, 0.02S / cm, 0.05S / cm, 0.08S / cm, 0.1S / cm, 0.15S / cm, 0.2S / cm, 0.3S / cm, 0.5S / cm, 0.6S / cm, 0.8S / cm, 1S / cm, and any value in the range composed of any two values, preferably 0.1-1S / cm.

[0097] In the present invention, the electronic conductivity parameter is measured by the AC impedance method. The specific test includes: sandwiching the sample to be tested between two electrolyte layers, measuring the electronic conductivity (σ') by electrochemical impedance spectroscopy (EIS), and calculating according to formula (2): Among them, R' b is the volume resistance of the sample to be tested (R' bDetermined by impedance spectrum), L and S are the thickness and area of ​​the sample to be tested.

[0098] In some embodiments of the present invention, preferably, the Li + Diffusion coefficient ≥10 - 10 cm 2 / s, preferably 10 -10 -10 -8 cm 2 / s, for example, 1×10 -10 cm 2 / s, 2×10 -10 cm 2 / s, 3×10 -10 cm 2 / s, 4×10 - 10 cm 2 / s, 5×10 -10 cm 2 / s, 6×10 -10 cm 2 / s, 8×10 -10 cm 2 / s, 1×10 -9 cm 2 / s, 2×10 -9 cm 2 / s, 5×10 - 9 cm 2 / s, 8×10 -9 cm 2 / s, 1×10 -8 cm 2 / s, and any value in the range of any two values.

[0099] In the present invention, Li + The diffusion coefficient parameters were measured by constant current gap titration (GITT).

[0100] In the present invention, the ionic conductivity parameters, electronic conductivity parameters and Li + The diffusion coefficient parameters were all tested at room temperature, which refers to 25±2°C.

[0101] In some embodiments of the present invention, preferably, the specific surface area of ​​the silicon-carbon negative electrode material is 0.5-5m 2 / g, for example, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, and any value in the range of any two values, preferably 0.8-2m 2 / g.

[0102] A second aspect of the present invention provides a method for preparing a silicon-carbon negative electrode material, the preparation method comprising:

[0103] (1) mixing a dispersion containing a conductive polymer with a silicon-carbon material matrix and performing a first drying to load the conductive polymer on the surface of the silicon-carbon material matrix to obtain a first intermediate;

[0104] (2) mixing the dispersion containing the metal salt mixture with the first intermediate and performing a second drying to load the metal salt mixture on the surface of the first intermediate to obtain a second intermediate;

[0105] (3) sintering the second intermediate in an inert atmosphere so that the conductive polymer is partially carbonized and the metal salt mixture is in situ converted into a catalyst containing LiF and Li α M β O γ A composite of a silicon-carbon anode material and a compatible connecting layer and an ion conductor layer are formed; wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time;

[0106] Wherein, the sintering temperature T> the melting point T of the metal salt mixture m , and the initial decomposition temperature of the conductive polymer is T d1 <the sintering temperature T<the complete decomposition temperature T of the conductive polymer d2 .

[0107] In the present invention, unless otherwise specified, the silicon-carbon material matrix, the conductive polymer, the metal salt mixture, the compatible connecting layer and the ion conductor layer are all in accordance with the above definitions, and the present invention will not elaborate on them herein.

[0108] In some embodiments of the present invention, preferably, in step (1), the mass ratio of the conductive polymer to the silicon-carbon material matrix is ​​0.1-5:100, for example, 0.1:100, 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100, 2.2:100, 2.5:100, 2.8:100, 3:100, 4:100, 5:100, and any value in the range composed of any two values, preferably 0.5-3:100.

[0109] In some embodiments of the present invention, preferably, the conductive polymer dispersion is obtained by first dispersing the conductive polymer and a first solvent; or, is obtained by polymerizing a conductive polymer monomer, an emulsifier, an oxidant and a first solvent.

[0110] In some embodiments of the present invention, preferably, the conductive polymer is selected from at least one of polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene), polypyridine, polyacetylene, poly(p-phenylene vinylene), modified polyacrylic acid, polythiophene, polyfuran, polycarbazole, polyphenylene sulfide and cross-linked polymers thereof.

[0111] In the present invention, the type of the first solvent depends on the type of the conductive polymer. When the conductive polymer is PPy or PEDOT, the first solvent is water-soluble, including but not limited to deionized water; when the conductive polymer is PANI, the first solvent is selected from organic solvents such as N-methylpyrrolidone and dimethylformamide.

[0112] In the present invention, the first dispersing conditions include: temperature of 15-40°C, preferably 20-30°C, time of 0.1-5h, preferably 0.5-2h; rotation speed of 100-500rpm, preferably 200-400rpm.

[0113] In the present invention, the first drying conditions include: temperature of 70-120° C., preferably 80-100° C.; time of 1-24 h, preferably 1-15 h.

[0114] In a specific embodiment of the present invention, in step (1), the conductive polymer is dispersed in a first solvent to form a uniform solution, and a silicon-carbon material matrix is ​​added to mix and first dried to load the conductive polymer on the surface of the silicon-carbon material matrix to obtain a first intermediate.

[0115] In another specific embodiment of the present invention, in step (1), the conductive polymer monomer and the emulsifier are dispersed in a first solvent, and then introduced into an oxidant for polymerization to form a uniform solution. Finally, a silicon-carbon material matrix is ​​added for mixing and a first drying to load the conductive polymer on the surface of the silicon-carbon material matrix to obtain a first intermediate.

[0116] In some embodiments of the present invention, preferably, in step (2), the mass ratio of the metal salt mixture to the silicon-carbon material matrix is ​​0.1-5:100, for example, 0.1:100, 0.2:100, 0.5:100, 0.6:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100, 2.2:100, 2.5:100, 2.8:100, 3:100, 3.2:100, 3.5:100, 3.8:100, 4:100, 5:100, and any value in the range composed of any two numerical values, preferably 0.2-4:100.

[0117] In some embodiments of the present invention, preferably, the dispersion containing the metal salt mixture is obtained by second dispersion of the metal salt mixture and a second solvent.

[0118] In some embodiments of the present invention, preferably, the metal salt mixture consists of at least Li, F, M, and O; further preferably, the metal salt mixture is selected from at least two of LiOH, LiNO3, Li2CO3, LiBF4, LiPF6, Li2C2O4, LiBOB, LiODFB, LiDFP, LiTFSI, Ca(TFSI)2, and Mg(TFSI)2.

[0119] In some embodiments of the present invention, preferably, the melting point T m ≤400°C, for example, 400°C, 380°C, 350°C, 300°C, 280°C, 250°C, 220°C, 200°C, 180°C, 150°C, and any value in the range consisting of any two values, preferably 180-380°C.

[0120] In the present invention, the concentration of the dispersion containing the metal salt mixture is 0.1-50 g / L, for example, 0.1 g / L, 1 g / L, 5 g / L, 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, and any value in the range consisting of any two values.

[0121] In the present invention, the second solvent is selected from at least one of ethanol, ethylene glycol, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), acetonitrile, ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC).

[0122] In the present invention, the conditions for the second dispersion include: temperature of 15-40°C, preferably 20-30°C, time of 0.1-5h, preferably 0.5-2h; rotation speed of 100-500rpm, preferably 200-400rpm.

[0123] In the present invention, the second drying conditions include: temperature of 70-120° C., preferably 80-100° C.; time of 1-24 h, preferably 1-15 h.

[0124] The method provided by the present invention is to control the sintering temperature T>T m And T>T d1 At this time, the metal salt mixture undergoes a melting reaction on the outer surface, and it is easier to form a uniform outer coating layer, that is, the ion conductor layer improves the ion conductivity, and the conductive polymer begins to be partially carbonized at this sintering temperature, which on the one hand enhances the interface compatibility between the outer coating layer and the silicon-carbon material matrix, and on the other hand improves the conductivity of the silicon-carbon negative electrode material. If the sintering temperature T <T m And T <T d1 , the metal salt mixture on the outer surface is difficult to undergo melting reaction, and an uneven and discontinuous island coating layer will be generated. The conductive polymer layer in the middle is difficult to carbonize, which not only affects the bridging effect but also reduces the conductivity of the material, ultimately affecting the material's cycle and rate performance.

[0125] In some embodiments of the present invention, preferably, in step (3), the sintering temperature T is 250-450°C, for example, 250°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, and any value in the range of any two values, preferably 300-420°C. In the present invention, the sintering temperature that meets the above range is intended to partially carbonize the conductive polymer to obtain a compatible connecting layer containing elemental carbon and the remaining conductive polymer; on the other hand, it is intended to convert the metal salt mixture in situ to obtain a conductive layer containing LiF and Li α M β O γ of the complex.

[0126] In some embodiments of the present invention, it is further preferred that the sintering temperature T and the melting point T of the metal salt mixture are m The temperature difference is 30-130° C., for example, 30° C., 50° C., 60° C., 80° C., 100° C., 120° C., 130° C., and any value in the range of any two values, preferably 50-130° C. Meeting the above temperature difference range can more effectively control the characteristic peak ratio, thereby improving the performance of the negative electrode material.

[0127] In some embodiments of the present invention, preferably, the sintering time is 1-10 h, for example, 1 h, 2 h, 3 h, 5 h, 8 h, 10 h, and any value in the range consisting of any two values, preferably 1-5 h.

[0128] The third aspect of the present invention provides an application of the silicon-carbon negative electrode material provided in the first aspect, or the silicon-carbon negative electrode material prepared by the preparation method provided in the second aspect in a lithium ion battery.

[0129] In the present invention, the lithium ion battery may be a liquid lithium ion battery or a solid lithium ion battery, preferably a solid lithium ion battery.

[0130] A fourth aspect of the present invention provides a negative electrode plate, which contains the silicon-carbon negative electrode material provided by the first aspect, or the silicon-carbon negative electrode material prepared by the preparation method provided by the second aspect.

[0131] In the present invention, the negative electrode plate comprises: a negative electrode current collector and a negative electrode coating loaded on the negative electrode current collector, wherein the negative electrode coating contains the silicon-carbon negative electrode material, conductive agent, and binder provided by the present invention, wherein the mass ratio of the silicon-carbon negative electrode material, conductive agent, and binder is 90-99:0.5-5:0.5-5.

[0132] In the present invention, the conductive agent is selected from at least one of gas-phase carbon nanotubes, conductive carbon black, carbon fiber, carbon nanotubes, acetylene black, Ketjen black, and graphene; the binder is selected from at least one of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), nitrile rubber (NBR), polyacrylonitrile (PAN), polyacrylic acid (PAA) and polyacrylate. In the present invention, polyacrylate includes but is not limited to polymethyl acrylate, polyethyl acrylate, and polypropyl acrylate.

[0133] A fifth aspect of the present invention provides a lithium-ion battery, comprising: a positive electrode plate, an electrolyte, and the negative electrode plate provided by the fourth aspect.

[0134] In the present invention, unless otherwise specified, the positive electrode plate comprises: a positive electrode current collector and a positive electrode coating loaded on the positive electrode current collector, wherein the positive electrode coating contains a positive electrode material, a conductive agent, and a binder, wherein the mass ratio of the positive electrode material, the conductive agent, and the binder is 90-99:0.5-5:0.5-5.

[0135] In the present invention, the positive electrode material is selected from the group consisting of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn0.3 O2 (abbreviated as NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) and its modified compounds, etc.

[0136] In the present invention, preferably, the electrolyte is selected from at least one of a liquid electrolyte, a sulfide electrolyte, a halide electrolyte and a polymer electrolyte, including but not limited to aLi2S·(100-a)P2S5 (0≤a≤100), Li3PS4, Li7P3S 11 、Li6PS5X (X is C1, Br or I) and its derivative systems, Li 10 M”P2S 12 (M" is Ge and / or Sn), Li 3.25 Ge 0.25 P 0.75 S4, Li4GeS4, Li 11 Sn2PS 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li3InCl6 and its derivative systems、Li 0.388 Ta 0.238 La 0.475 Cl3 and its derivative systems, Li5X3M”'2O 12 (M'' is Ta and / or Nb), Li7La3Zr2O 12 and its derivative systems, La 2 / 3-δ Li 3δ At least one of TiO3 (0<δ<2 / 3) and its derivative systems, NaZr2(PO4)3 and its derivative systems, polyethylene oxide (PEO) and its derivatives, polypropylene carbonate (PPC), polyacrylonitrile (PAN), polydimethylsiloxane (PDMS), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA) and its derivative systems and LiBH4.

[0137] In the present invention, it is further preferred that the electrolyte is selected from a sulfide electrolyte. The silicon-carbon negative electrode material provided by the present invention is applied to a sulfide all-solid-state battery, which effectively improves the material interface stability and ion transmission capacity, and the sulfide all-solid-state lithium-ion battery assembled with the negative electrode has greatly improved cycle and rate performance.

[0138] The present invention will be described in detail below through examples.

[0139] The silicon-carbon material matrix P1 is composed of porous carbon, amorphous silicon inside the porous carbon, and a carbon layer on the surface of the porous carbon. The specific surface area of ​​the porous carbon is 1750 m 2 / g, pore volume is 0.84cc / g, microporosity / mesoporosity is 6.65; the grain size of amorphous silicon is 1.9nm; and the thickness of the carbon layer is 2nm.

[0140] Based on the above silicon-carbon material matrix P1, the silicon content is 55wt%, the carbon content is 45wt%, D 50 8μm, tap density 0.95g / cm 3 , with a specific surface area of ​​1.62m 2 / g.

[0141] The XRD pattern of the silicon-carbon material matrix P1 is as follows: Figure 2 As shown, a broad characteristic peak appears at 2θ=28±1°, indicating that the silicon-carbon material matrix P1 contains amorphous silicon.

[0142] The silicon-carbon material matrix P2 is composed of porous carbon and amorphous silicon located inside the porous carbon; the specific surface area of ​​the porous carbon is 1750m 2 / g, pore volume is 0.84cc / g, microporosity / mesoporosity is 5.5; the grain size of amorphous silicon is 1.9nm.

[0143] Based on the above silicon-carbon material matrix P2, the silicon content is 55wt%, the carbon content is 45wt%, D 50 The diameter is 7.7 μm and the tap density is 0.9 g / cm 3 , with a specific surface area of ​​4.8m 2 / g.

[0144] Example 1

[0145] (1) Disperse 1.25 g of hexadecyltrimethylammonium bromide (CTAB) in 2 L of deionized water and stir for 0.5 h to form a uniform transparent solution; add 100 g of silicon-carbon material matrix P1 and stir and disperse at a speed of 200 rpm for 1 h; dropwise add 0.035 mL of PPy monomer and continue stirring at the same speed for 2 h, then add 6.5 g of oxidant (NH4)2S2O8, wait for the PPy monomer to react and polymerize for 8 h, filter and wash the resulting reactant 3 times, and then place it in a constant temperature oven at 70 ° C for 12 h to load PPy (conductivity is 20 S / cm, weight average molecular weight is 50000 g / mol) on the surface of the silicon-carbon material matrix P1 to obtain a first intermediate;

[0146] (2) Weigh 0.2362 g of LiOH and 0.2638 g of LiBF4 powder in turn, grind them evenly in a dry room, and completely dissolve them in anhydrous ethanol to form a dispersion with a concentration of 20 g / L;

[0147] 50 g of the first intermediate was uniformly dispersed in anhydrous ethanol, the dispersion was added dropwise during stirring at 200 rpm, and the mixture was evaporated to dryness under stirring at 85° C., so as to load LiOH and LiBF4 on the surface of the first intermediate to obtain a second intermediate;

[0148] (3) The second intermediate was transferred to a tubular furnace and sintered at 400° C. for 4 h in a nitrogen atmosphere to obtain a silicon-carbon negative electrode material S1.

[0149] Among them, the DSC graph of the mixture of LiOH and LiBF4 and PPy is as follows Figure 3 As shown, the melting point of the mixture of LiOH and LiBF4 is T m is 320℃, the initial decomposition temperature of PPy is T d1 The complete decomposition temperature is 360°C. d2 It is 460℃.

[0150] The SEM image and EDS distribution image of the silicon-carbon negative electrode material S1 are as follows: Figure 4-5 As shown, the surface of the silicon-carbon negative electrode material S1 is smooth and flat, forming a uniform and effective compatible connection layer and ion conductor layer; wherein, the ion conductor layer contains B, F and O elements, and the uniform and rich distribution of F and O elements on the surface fully demonstrates the uniformity of the ion conductor layer.

[0151] Among them, the Raman spectrum of the above silicon-carbon negative electrode material S1 is as follows Figure 6 As shown, at 1350±20cm -1 and 1580±20cm -1 There are Raman responses in the wavenumber range, corresponding to characteristic peaks D and G respectively.

[0152] Example 2

[0153] (1) 1.0 g of PANI (conductivity of 4.05 S / cm, weight average molecular weight of 40,000 g / mol) was dispersed in 100 mL of DMF, and the mixture was stirred and dispersed at a speed of 200 rpm for 0.5 h to form a uniform transparent solution, and then 100 g of silicon-carbon material matrix P1 was added, and the mixture was stirred at the same speed for 2 h, and then placed in a constant temperature oven at 80° C. for 12 h to load PANI on the surface of the silicon-carbon material matrix P1 to obtain a first intermediate;

[0154] (2) Weigh 0.2362 g of LiOH and 0.2638 g of LiBF4 powder in turn, grind them evenly in a dry room, and completely dissolve them in anhydrous ethanol to form a dispersion with a concentration of 20 g / L;

[0155] 50 g of the first intermediate was uniformly dispersed in anhydrous ethanol, the dispersion was added dropwise during stirring at 200 rpm, and the mixture was evaporated to dryness under stirring at 85° C., so as to load LiOH and LiBF4 on the surface of the first intermediate to obtain a second intermediate;

[0156] (3) The second intermediate was transferred to a tubular furnace and sintered at 400° C. for 4 h in a nitrogen atmosphere to obtain a silicon-carbon negative electrode material S2.

[0157] Among them, the melting point of the mixture of LiOH and LiBF4 is T m The initial decomposition temperature of PANI is 320℃. d1 The complete decomposition temperature is 240℃. d2 It is 480℃.

[0158] Example 3

[0159] (1) 1.0 g of PEDOT (conductivity of 2.3 S / cm, weight average molecular weight of 200,000 g / mol) was dispersed in 100 mL of deionized water, and stirred at a speed of 200 rpm for 0.5 h to form a uniform transparent solution, and then 100 g of silicon-carbon material matrix P1 was added, and the solution was stirred for 2 h at the same speed, and then placed in a constant temperature oven at 80° C. for 12 h to load PEDOT on the surface of the silicon-carbon material matrix P1 to obtain a first intermediate;

[0160] (2) Weigh 0.2362 g of LiOH and 0.2638 g of LiBF4 powder in turn, grind them evenly in a dry room, and completely dissolve them in anhydrous ethanol to form a dispersion with a concentration of 20 g / L;

[0161] 50 g of the first intermediate was uniformly dispersed in anhydrous ethanol, the dispersion was added dropwise during stirring at 200 rpm, and the mixture was evaporated to dryness under stirring at 85° C., so as to load LiOH and LiBF4 on the surface of the first intermediate to obtain a second intermediate;

[0162] (3) The second intermediate was transferred to a tubular furnace and sintered at 400° C. for 4 h in a nitrogen atmosphere to obtain a silicon-carbon negative electrode material S3.

[0163] Among them, the melting point of the mixture of LiOH and LiBF4 is T m The initial decomposition temperature of PEDOT is 320°C. d1 The complete decomposition temperature is 200°C. d2 It is 440℃.

[0164] Example 4

[0165] According to the method of Example 1, the difference is that

[0166] In step (3), the sintering temperature is replaced with 370°C;

[0167] The other conditions are the same to obtain silicon-carbon negative electrode material S4.

[0168] Example 5

[0169] According to the method of Example 1, the difference is that

[0170] In step (3), the sintering temperature is replaced with 450°C;

[0171] The other conditions are the same to obtain silicon-carbon negative electrode material S5.

[0172] Example 6

[0173] According to the method of Example 1, the difference is that

[0174] In step (2), 0.2362 g of LiOH and 0.2638 g of LiBF4 are replaced by 0.3059 g of LiOH and 0.1941 g of LiPF6, and the melting points of LiOH and LiPF6 are T m 300℃;

[0175] In step (3), LiOH and LiPF6 are converted in situ into a composite containing LiF, Li3PO4 and Li2O;

[0176] The other conditions are the same to obtain silicon-carbon negative electrode material S6.

[0177] Example 7

[0178] According to the method of Example 1, the difference is that

[0179] In step (2), 0.2362 g of LiOH and 0.2638 g of LiBF4 are replaced by 0.1332 g of LiNO3 and 0.3668 g of LiTFSI, and the melting points of LiNO3 and LiTFSI are T m 280℃;

[0180] In step (3), LiNO3 and LiTFSI are converted in situ into a composite containing LiF, Li2O and Li2S;

[0181] The other conditions are the same to obtain silicon-carbon negative electrode material S7.

[0182] Example 8

[0183] According to the method of Example 1, the difference is that

[0184] In step (2), the amount of LiOH was replaced by 0.0709 g, and the amount of LiBF4 was replaced by 0.0791 g;

[0185] The other conditions are the same to obtain silicon-carbon negative electrode material S8.

[0186] Example 9

[0187] According to the method of Example 1, the difference is that

[0188] In step (2), the amount of LiOH was replaced by 0.7086 g, and the amount of LiBF4 was replaced by 0.7914 g;

[0189] The other conditions are the same to obtain silicon-carbon negative electrode material S9.

[0190] Example 10

[0191] According to the method of Example 1, the difference is that

[0192] In step (1), the amount of PPy monomer was replaced with 0.175 mL;

[0193] The other conditions are the same to obtain the silicon-carbon negative electrode material S10.

[0194] Embodiment 11

[0195] According to the method of Example 1, the difference is that

[0196] In step (1), the amount of PPy monomer was replaced with 0.0035 mL;

[0197] The other conditions are the same to obtain the silicon-carbon negative electrode material S11.

[0198] Example 12

[0199] According to the method of Example 1, the difference is that

[0200] In step (1), 100 g of silicon-carbon material substrate P1 is replaced with 100 g of silicon-carbon material substrate P2;

[0201] The other conditions are the same to obtain silicon-carbon negative electrode material S12.

[0202] Comparative Example 1

[0203] 100 g of the silicon-carbon material substrate P1 was directly placed in a tubular furnace and sintered at 400° C. for 4 h in a nitrogen atmosphere to obtain the silicon-carbon negative electrode material DS1.

[0204] Comparative Example 2

[0205] The method of Example 1 is followed, except that step (2) is omitted, i.e.,

[0206] Directly subjecting the first intermediate obtained in step (1) to step (3);

[0207] The other conditions are the same to obtain the silicon-carbon negative electrode material DS2.

[0208] Comparative Example 3

[0209] The method of Example 1 is followed, except that step (1) is omitted, that is, in step (2), 50 g of the first intermediate is replaced with 50 g of the silicon-carbon material substrate P1;

[0210] The other conditions were the same to obtain the silicon-carbon negative electrode material DS3.

[0211] Comparative Example 4

[0212] According to the method of Example 1, the difference is that

[0213] In step (3), the sintering temperature is replaced with 200°C;

[0214] The other conditions are the same to obtain silicon-carbon negative electrode material DS4.

[0215] Comparative Example 5

[0216] According to the method of Example 1, the difference is that

[0217] In step (3), the sintering temperature is replaced with 600°C;

[0218] The other conditions are the same to obtain the silicon-carbon negative electrode material DS5.

[0219] Comparative Example 6

[0220] According to the method of Example 1, the difference is that

[0221] In step (1), the type of conductive polymer is changed, that is,

[0222] Replace PPy with starch;

[0223] The other conditions were the same to obtain the silicon-carbon negative electrode material DS6.

[0224] Table 1

[0225]

[0226] Note: 1- mass ratio of conductive polymer and silicon carbon material matrix;

[0227] 2-Mass ratio of the metal salt mixture to the silicon-carbon material matrix;

[0228] 3- When the sintering temperature T> the melting point T of the metal salt mixture m , then the species contains LiF and Li α M β O γ otherwise, it is a mixture of metal salts;

[0229] In the 4-complex, LiF and Li α M β O γ molar ratio.

[0230] Table 1

[0231]

[0232]

[0233] It can be seen from the results in Table 1 that compared with Comparative Examples 1-6, Examples 1-12 use the silicon-carbon negative electrode material provided by the present invention, that is, sequentially construct a specific compatibility connection layer and a specific ion conductor layer on the surface of the silicon-carbon material matrix, and combine with a specific sintering temperature, which can effectively improve the ionic conductivity, electronic conductivity and Li of the silicon-carbon negative electrode material. + Diffusion coefficient.

[0234] Test Example 1

[0235] The silicon-carbon negative electrode materials obtained in Examples 1-12 and Comparative Examples 1-6 were used as active materials for negative electrode plates of batteries and were respectively prepared and assembled into liquid button batteries; wherein the specific preparation process of each liquid battery is as follows:

[0236] Preparation of negative electrode sheets for batteries: Add a binder to deionized water to prepare a glue solution. Then, the silicon-carbon negative electrode materials (S1-S12 and DS1-DS6) obtained in Examples 1-12 and Comparative Examples 1-6 as active materials for negative electrode sheets for batteries and conductive agents are added to the above-mentioned glue solution, stirred and slurried, and finally the obtained slurry is evenly coated on the copper foil with a scraper, and each button-type battery negative electrode sheet is obtained after drying, rolling and cutting; wherein, the binder is LA133 binder, the conductive agent is SP (conductive carbon black), the solvent is deionized water, and the feed ratio satisfies the following conditions: silicon-carbon negative electrode material: SP: LA133: deionized water = 80g: 10g: 10g: 120mL;

[0237] Preparation of liquid button cells: the electrolyte used was a LiPF6 solution with a concentration of 1 mol / L, and the solvent used was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a weight ratio of 1:1; a metal lithium sheet was used as the counter electrode, and a polypropylene (PP) film was used as the diaphragm. The entire battery assembly process was carried out in an argon-filled glove box, and the electrochemical performance was performed on a Wuhan Blue Electric CT2001A battery tester. The test conditions were: the charge and discharge voltage range was 0.005V to 0.8V, and the charge and discharge rate was 0.1C. The first reversible specific capacity and the first efficiency were calculated, and the test results are shown in Table 2 below.

[0238] At the same time, the above-mentioned liquid button battery is subjected to a full-charge expansion test. The specific test process is: for the negative electrode plate of the button battery after rolling, a screw micrometer is used to test the thickness H1 of the negative electrode plate. Then, the button battery is fully charged to 100% SOC state at a rate of 0.1C and the negative electrode plate is disassembled. The screw micrometer is used again to test the thickness H2 of the negative electrode plate. Then, the full-charge expansion rate of the plate is calculated = (H2H1) / H1×100%. The test results are shown in Table 2 below.

[0239] Test Example 2

[0240] The silicon-carbon negative electrode materials obtained in Examples 1-12 and Comparative Examples 1-6 were used as active materials for the negative electrode plates of the battery and were respectively prepared and assembled into solid-state button batteries; wherein the specific preparation process of each solid-state battery is as follows:

[0241] The silicon-carbon negative electrode materials (S1-S12 and DS1-DS6) obtained in Examples 1-12 and Comparative Examples 1-6 are used as active materials for negative electrode sheets of batteries. The active materials are fully ground, mixed and pressed with LiP6S5Cl, VGCF and PTFE in a mass ratio of 65:32:2:1 to form a composite negative electrode. The negative electrode is then placed in a polyetheretherketone tube with a diameter of 10 mm. 100 mg of LiP6S5Cl is then weighed and added to the tube. The tube is pressed under an external pressure of 300 MPa to ensure that the solid electrolyte layer is in close contact with the negative electrode sheet. Finally, a lithium indium alloy sheet is added to the other side of the solid electrolyte LiP6S5Cl, and the mixture is further pressed under an external pressure of 40 MPa to prepare a half-cell with a three-layer composite structure. The test conditions are as follows: the half-cell is under a pressure of 70 MPa, the charge and discharge voltage range is 0.61 to 1.5 V, the charge and discharge rate is 0.1C, the first reversible specific capacity is calculated, and the rate test is carried out with a test system of 0.05C / 0.05C cycle for one week, 0.1C / 0.1C cycle for 3 weeks, 0.2C / 0.2C cycle for 3 weeks, 0.33C / 0.33C cycle for 3 weeks, 0.5C / 0.5C cycle for 3 weeks, 0.7C / 0.7C cycle for 3 weeks, and 1C / 1C cycle for 3 weeks. The test results are shown in Table 2 below.

[0242] Among them, the sulfide solid-state half-cell rate-cycle performance diagram assembled from the silicon-carbon negative electrode material S1 prepared in Example 1 is as follows Figure 7 As shown, the silicon-carbon negative electrode material S1 has higher rate performance and cycle performance, especially higher 0.5C capacity retention rate.

[0243] Table 2

[0244]

[0245] It can be seen from the results in Table 2 that, compared with Comparative Examples 1-6, the lithium-ion batteries assembled using the silicon-carbon negative electrode materials provided by the present invention in Examples 1-12 not only have a low volume expansion rate, but also have excellent electrochemical properties, that is, high initial efficiency, high rate performance and high cycle performance.

[0246] Compared with Example 1 and Comparative Examples 1-3, it is known that when the surface of the silicon-carbon material substrate is not coated or only coated with a compatible connecting layer or only coated with an ion conductor layer, it is difficult to achieve performance improvement. That is, when Comparative Example 2 is only coated with a compatible connecting layer, the ionic conductivity of this layer is not high, and it is difficult to achieve the effect of reducing the lithium ion diffusion barrier. When Comparative Example 3 is only coated with an ion conductor layer, the interface bonding force between the surface of the silicon-carbon material substrate and the ion conductor layer is poor, and it is difficult to form a uniform and effective coating layer (easy to fall off during the cycle), thereby losing the important role of protecting the silicon-carbon material substrate and improving the ion conductivity. Therefore, only according to the present invention, the compatible connecting layer and the ion conductor layer are constructed on the surface of the silicon-carbon material substrate in turn, and the synergistic effect between the two functional layers is brought into play, that is, the compatible connecting layer constructs a bridge and bond between the surface of the silicon-carbon material substrate and the ion conductor layer to enhance the bonding force between the two, and the outer surface ion conductor layer is uniformly and effectively coated, which is conducive to reducing the lithium ion transmission barrier and significantly improving the lithium ion transmission kinetics, so that the electrochemical properties of the material can be fully utilized.

[0247] Comparing Example 1 with Examples 4-5 and Comparative Examples 4-5, it can be seen that as the sintering temperature increases, the electrochemical performance of the battery shows a trend of first increasing and then decreasing. This is because when the sintering temperature is low, the compatibility connection layer does not undergo the expected carbonization, resulting in the ion conductor layer and the silicon-carbon material matrix having a good bonding force, but the carbonization degree of the conductive polymer is too low or not carbonized, thereby reducing the conductivity of the silicon-carbon negative electrode material and the rate performance of the battery, and the metal salt mixture does not undergo a melting reaction and is difficult to form an ion conductor layer, resulting in poor lithium ion transmission performance and high interface impedance. When the sintering temperature is too high, the carbonization degree of the conductive polymer is too high, reducing the interfacial bonding force between the matrix and the ion conductor layer, affecting the structural stability of the silicon-carbon negative electrode material, thereby reducing the cycle performance of the battery, and the grain size of the amorphous silicon inside the silicon-carbon material matrix becomes larger, and the intrinsic performance of the matrix is ​​destroyed. The ion conductor layer also has a phenomenon of particle aggregation, which slows down the lithium ion transmission and leads to a decrease in rate performance.

[0248] Comparing Example 1 with Examples 6-7, it can be seen that as the type of the metal salt mixture changes, the generated ion conductor layer product also changes, and the rate performance of the battery shows certain differences, which is caused by the different intrinsic conductivities of different ion conductor materials.

[0249] Compared with Example 1 and Examples 8-9, it can be seen that as the thickness of the ion conductor layer increases, the reversible capacity of the material increases first and then decreases slightly. This is because the ion conductor layer itself does not serve as a lithium storage material. When its thickness is too high, the capacity of the material will be reduced. When the thickness is too small, the interface side reaction is relatively large, resulting in a relatively low reversible capacity. That is, when the thickness of the ion conductor layer is small, it is difficult to play a good role in improving the ionic conductivity of the material and reducing the interface barrier. When the thickness of the ion conductor layer is too thick, due to the poor electronic conductivity of the ion conductor layer, it is difficult to give full play to the rate performance of the material.

[0250] Compared with Example 1 and Example 10-11, it can be seen that as the thickness of the compatible connecting layer increases, the reversible capacity of the material increases first and then decreases slightly. This is because the compatible connecting layer itself is not used as a lithium storage material. When the thickness of the compatible connecting layer is too high, the capacity of the material will be reduced. When the thickness is too small, the interface side reaction is relatively large, resulting in a low reversible capacity. That is, when the thickness of the compatible connecting layer is small, it is difficult to play a good bridging role, and the interface bonding force deteriorates, making the ion conductor layer easy to fall off during the cycle, resulting in a decrease in rate performance. When the thickness of the compatible connecting layer is too thick, it is easy to cause poor ion / electron transmission, affecting the material capacity and the material rate performance is difficult to give full play.

[0251] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a silicon-carbon material matrix, and a compatible connecting layer and an ion conductor layer sequentially coated on the surface of the matrix; the compatible connecting layer is a partially carbonized conductive polymer and a remaining conductive polymer, and the ion conductor layer is a conductive polymer containing LiF and Li α M β O γ A complex of, wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time; The silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.3-2.2, and I(D) and I(G) respectively represent the silicon-carbon negative electrode material in the Raman spectrum, corresponding to 1330-1370cm -1 and 1560-1610cm -1 The intensity of characteristic peak D and characteristic peak G in the wavenumber range.

2. The silicon-carbon negative electrode material according to claim 1, wherein Based on the total weight of the silicon-carbon material matrix, the silicon content is 45-65wt%, preferably 50-60wt%; the carbon content is 35-55wt%, preferably 40-50wt%; Preferably, the D of the silicon-carbon material matrix 50 1-15 μm, preferably 3-8 μm; Preferably, the tap density of the silicon-carbon material matrix is ​​0.5-2 g / cm 3 , preferably 0.81.2g / cm 3 ; Preferably, the specific surface area of ​​the silicon-carbon material matrix is ​​0.55 m 2 / g, preferably 0.5-3m 2 / g.

3. The silicon-carbon negative electrode material according to claim 1 or 2, wherein: The silicon-carbon material matrix includes porous carbon and amorphous silicon located inside the porous carbon; Preferably, the specific surface area of ​​the porous carbon is ≥1500m 2 / g, preferably 1700-2200m 2 / g; Preferably, the pore volume of the porous carbon is 0.75-1.05 cc / g, preferably 0.8-0.95 cc / g; Preferably, the microporosity / mesoporosis of the porous carbon is ≥4, preferably 5-7; wherein the microporosity refers to the volume ratio of micropores with a pore diameter of <2 nm to the total pores, and the mesoporosity refers to the volume ratio of mesopores with a pore diameter of 2-50 nm to the total pores; Preferably, the silicon-carbon material matrix further comprises a carbon layer located on the surface of the porous carbon; Preferably, the thickness of the carbon layer is 2-10 nm, preferably 3-8 nm.

4. The silicon-carbon negative electrode material according to any one of claims 1 to 3, wherein: The silicon-carbon negative electrode material satisfies: I(D) / I(G) is 0.4-1.5, preferably 0.5-1.2; Preferably, in the compatible connection layer, one end of the remaining conductive polymer forms a chemical bond with the silicon-carbon material matrix through cross-linking; Preferably, the conductivity of the conductive polymer is 0.01-120 S / cm, preferably 0.1-100 S / cm; Preferably, the weight average molecular weight of the conductive polymer is 10 2 -10 6 g / mol, preferably 10 3 -10 5 g / mol; Preferably, the conductive polymer is selected from at least one of polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene), polypyridine, polyacetylene, poly(p-phenylene vinylene), modified polyacrylic acid, polythiophene, polyfuran, polycarbazole, polyphenylene sulfide and cross-linked polymers thereof.

5. The silicon-carbon negative electrode material according to any one of claims 1 to 4, wherein: In the composite, Li α M β O γ Selected from Li2O, Li3P, Li3PO4, L2S, Li2SO4 and Li x B y O z At least one of the following, where 1≤x≤3, 1≤y≤4, 2≤z≤7; Preferably, in the composite, LiF and Li α M β O γ The molar ratio is 1:(0.05-1), preferably 1:(0.06-0.6); Preferably, the composite is prepared by sintering a metal salt mixture containing at least Li, F, M, and O in an inert atmosphere; Preferably, the metal salt mixture is selected from at least two of LiOH, LiNO3, Li2CO3, LiBF4, LiPF6, Li2C2O4, LiBOB, LiODFB, LiDFP, LiTFSI, Ca(TFSI)2 and Mg(TFSI)2; Preferably, the sintering temperature T> the melting point T of the metal salt mixture m , and the initial decomposition temperature of the conductive polymer is T d1 <the sintering temperature T<the complete decomposition temperature T of the conductive polymer d2 .

6. The silicon-carbon negative electrode material according to any one of claims 1 to 5, wherein: The thickness of the compatible connecting layer is 1-10 nm, preferably 2-5 nm; Preferably, the thickness of the ion conductor layer is 1-10 nm, preferably 2-4 nm; Preferably, the ionic conductivity of the silicon-carbon negative electrode material is ≥10 -8 S / cm, preferably 10 -8 -10 -7 S / cm; Preferably, the electronic conductivity of the silicon-carbon negative electrode material is ≥0.01S / cm, preferably 0.1-1S / cm; Preferably, the Li of the silicon-carbon negative electrode material + Diffusion coefficient ≥10 -10 cm 2 / s, preferably 10 -10 -10 -8 cm 2 / s; Preferably, the specific surface area of ​​the silicon-carbon negative electrode material is 0.5-5m 2 / g, preferably 0.8-2m 2 / g.

7. A method for preparing a silicon-carbon negative electrode material, characterized in that: The preparation method comprises: (1) mixing a dispersion containing a conductive polymer with a silicon-carbon material matrix and performing a first drying to load the conductive polymer on the surface of the silicon-carbon material matrix to obtain a first intermediate; (2) mixing the dispersion containing the metal salt mixture with the first intermediate and performing a second drying to load the metal salt mixture on the surface of the first intermediate to obtain a second intermediate; (3) sintering the second intermediate in an inert atmosphere so that the conductive polymer is partially carbonized and the metal salt mixture is in situ converted into a catalyst containing LiF and Li α M β O γ A composite of a silicon-carbon anode material and a compatible connecting layer and an ion conductor layer are formed; wherein M is selected from at least one of B, S and P, 1≤α≤3, 0≤β≤5, 0≤γ≤10, and β and γ are not 0 at the same time; Wherein, the sintering temperature T> the melting point T of the metal salt mixture m , and the initial decomposition temperature of the conductive polymer is T d1 <the sintering temperature T<the complete decomposition temperature T of the conductive polymer d2 .

8. The preparation method according to claim 7, wherein: In step (1), The mass ratio of the conductive polymer to the silicon-carbon material matrix is ​​0.1-5:100, preferably 0.5-3:100; Preferably, the conductive polymer dispersion is obtained by first dispersing the conductive polymer and the first solvent; or, is obtained by polymerizing the conductive polymer monomer, the emulsifier, the oxidant and the first solvent; Preferably, the conductive polymer is selected from at least one of polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene), polypyridine, polyacetylene, poly(p-phenylene vinylene), modified polyacrylic acid, polythiophene, polyfuran, polycarbazole, polyphenylene sulfide and cross-linked polymers thereof.

9. The preparation method according to claim 7 or 8, wherein: In step (2), The mass ratio of the metal salt mixture to the silicon-carbon material matrix is ​​0.1-5:100, preferably 0.2-4:100; Preferably, the dispersion containing the metal salt mixture is obtained by second dispersion of the metal salt mixture and a second solvent; Preferably, the metal salt mixture consists of at least Li, F, M, O, preferably at least two selected from LiOH, LiNO3, Li2CO3, LiBF4, LiPF6, Li2C2O4, LiBOB, LiODFB, LiDFP, LiTFSI, Ca(TFSI)2 and Mg(TFSI)2; Preferably, the melting point T of the metal salt mixture is m ≤400°C, preferably 180-380°C.

10. The preparation method according to any one of claims 7 to 9, wherein: In step (3), the sintering temperature T is 250-450°C, preferably 300-420°C; Preferably, the sintering temperature T and the melting point T of the metal salt mixture are m The temperature difference is 30-130°C, preferably 50-130°C; Preferably, the sintering time is 1-10 h, preferably 1-5 h.

11. Use of the silicon-carbon negative electrode material according to any one of claims 1 to 6, or the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 7 to 10 in lithium-ion batteries.

12. A negative electrode plate, characterized in that: The negative electrode plate contains the silicon-carbon negative electrode material described in any one of claims 1-6, or the silicon-carbon negative electrode material prepared by the preparation method described in any one of claims 7-10.

13. A lithium ion battery, characterized in that: The lithium-ion battery comprises: a positive electrode plate, an electrolyte, and the negative electrode plate according to claim 12; Preferably, the electrolyte is selected from at least one of a liquid electrolyte, an oxide electrolyte, a sulfide electrolyte, a halide electrolyte and a polymer electrolyte, and is preferably a sulfide electrolyte.

Citation Information

Patent Citations

  • Porous silicon carbon material coated with solid electrolyte layer and preparation method and application of porous silicon carbon material

    CN118016985A

Cited By

  • Synergistic modified silicon-carbon negative electrode material, preparation method thereof, negative electrode and battery

    CN122246113A

  • Synergistically modified silicon-carbon negative electrode material, preparation method thereof, negative electrode and battery

    CN122246113B